Could a Focus on the “Why” of Taxonomy Help Taxonomy Better Respond to the Needs of Science and Society? - Pritchard, Leighton; Brown, C. Titus; Harrington, Bailey; Heath, Lenwood S.; Pierce-Ward, N. Tessa; Vinatzer, Boris A. (Frontiers in Microbiology, 2022)
Genomics has put prokaryotic rank-based taxonomy on a solid phylogenetic foundation. However, most taxonomic ranks were set long before the advent of DNA sequencing and genomics. In this concept paper, we thus ask the following question: Should prokaryotic classification schemes besides the current phylum-to-species ranks be explored, developed, and incorporated into scientific discourse? Could such alternative schemes provide better solutions to the basic need of science and society for which taxonomy was developed, namely, precise and meaningful identification? A neutral genome-similarity based framework is then described that could allow alternative classification schemes to be explored, compared, and translated into each other without having to choose only one as the gold standard. Classification schemes could thus continue to evolve and be selected according to their benefits and based on how well they fulfill the need for prokaryotic identification.